Assessment of N95 and K95 respirator decontamination: fiber integrity, filtration efficiency, and dipole charge density. - Yim, Wonjun (medRxiv, 2020)
Personal protective equipment (PPE) including N95 respirators are critical for persons exposed to SARS-CoV-2. KN95 respirators and N95 decontamination protocols have been described as solutions to a lack of such PPE. However, there are a few materials science studies that characterize the charge distribution and physical changes accompanying disinfection treatments particularly heating. Here, we report the filtration efficiency, dipole charge density, and fiber integrity of pristine N95 and KN95 respirators before and after various decontamination methods. We found that the filter layer of N95 is 8-fold thicker than that of KN95, which explains its 10% higher filtration efficiency (97.03 %) versus KN95 (87.76 %) under pristines condition. After 60 minutes of 70 °C treatment, the filtration efficiency and dipole charge density of N95 became 97.16% and 12.48 µC/m2, while those of KN95 were 83.64% and 1.48 µC/m2 ; moreover, fit factor of N95 was 55 and that of KN95 was 2.7. In conclusion, the KN95 respirator is an inferior alternative of N95 respirator. In both systems, a loss of electrostatic charge does not directly correlate to a decrease in performance.